Construction and theoretical insights into the ESIPT fluorescent probe for imaging formaldehyde in vitro and in vivo. Issue 28 (10th March 2021) - Bi, Anyao; Liu, Min; Huang, Shuai; Zheng, Fan; Ding, Jipeng; Wu, Junyong; Tang, Gao; Zeng, Wenbin
Abstract : Schematic illustration of construction and theoretical insight studies with the ESIPT fluorescent probe for formaldehyde detection in cells and the AD brain model. Abstract : We report the first ESIPT-based probe ABTB, for the highly sensitive and selective imaging of formaldehyde (FA). The various theoretical calculations have been systematically performed, and clearly unravel the lighting mechanism of the fluorescent probe for FA. Additionally, the probe was successfully applied in monitoring endogenous FA in the brain of AD mice.